ʺDevelopment of STEM education in Ukraineʺ - Drokina, A. (Problems of Engineer-Pedagogical Education, 2024)
The article discusses the key issues of STEM education development in Ukraine. On the basis of a thorough analysis of scientific, pedagogical and regulatory sources, the author highlights the key processes of development of STEM education in our country and identifies current trends in the implementation of STEM education at the current stage of its development. The essence of the main concepts is investigated in the paper: "STEM education", "STEM training". It is found that in Ukraine, STEM education is organised in accordance with the Action Plan for Implementation of the Concept for the Development of Science and Mathematics Education (STEM Education) until 2027 and is based on the implementation of the State reform "New Ukrainian School". In view of this, it is emphasised that STEM education in our country is an integral part of the New Ukrainian School, as it involves not only the acquisition of knowledge but also aims to develop competences of students. Based on the priority areas for the development of STEM education at the national and regional levels, it is found that in our country they include: development of scientific and methodological support and special teaching aids; training and professional development of scientific and pedagogical staff; expansion of the network of regional STEM centres/laboratories; creation of an information base for the development of STEM education in Ukraine using IT technologies, etc. The attention is focused on the fact that one of the most important tasks for the successful implementation of STEM education in Ukraine is the training of competitive, highly qualified teachers. It is determined that the professional and pedagogical training of future teachers in pedagogical institutions of higher education should be carried out as a purposeful, systematic and organised process. It is worth noting that this process necessarily requires periodic updating of curricula, improvement of work programmes of educational components, development of practice-oriented teaching methods, etc. It is proved that digitalisation opens up innovative prospects for the development of STEM education, contributing to improving the quality of modern education and preparing the younger generation for the challenges of the modern world in the context of rapid technological progress. It has been determined that digital technologies provide a significant number of powerful tools and resources that help to optimise the modern educational process in the implementation of STEM education. The introduction of virtual laboratories, simulations, gaming platforms, and much more makes the process of education even more innovative, effective, and interesting for students.